1999
DOI: 10.3109/10623329909165308
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Functional Leukocyte-Type NADPH Oxidase in Human Endothelial Cells : A Potential Atherogenic Source of Reactive Oxygen Species

Abstract: Cultured human endothelial cells (EC) exposed to atherogenic low-density lipoprotein levels have increased reactive oxygen species (ROS) generation. The enzyme responsible for this ROS production elevation is unknown. We have examined for the presence of a functional leukocyte-type NADPH oxidase in EC to elucidate whether this enzyme could be the ROS source. The plasma membrane fraction of disrupted EC showed a reduced-minus-oxidized difference spectra with absorption peaks identical to those observed in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 32 publications
5
101
0
2
Order By: Relevance
“…These findings also support the presence of a functionally active leukocyte type NADPH oxidase in EC. 27) From these facts, it is likely that fluvastatin inhibits the progression of atherosclerosis via the inhibition of NADPH oxidase in not only neutrophils but also in EC. Rueckschloss et al reported that oxidized LDL induces proatherosclerotic NADPH oxidase expression and superoxide anion formation in human endothelial cells, and an antioxidative potential of HMG-CoA reductase inhibition via the reduction of vascular NADPH oxidase expression.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also support the presence of a functionally active leukocyte type NADPH oxidase in EC. 27) From these facts, it is likely that fluvastatin inhibits the progression of atherosclerosis via the inhibition of NADPH oxidase in not only neutrophils but also in EC. Rueckschloss et al reported that oxidized LDL induces proatherosclerotic NADPH oxidase expression and superoxide anion formation in human endothelial cells, and an antioxidative potential of HMG-CoA reductase inhibition via the reduction of vascular NADPH oxidase expression.…”
Section: Discussionmentioning
confidence: 99%
“…Apocynin is a strong oxidative inhibitor that has been demonstrated to block NADPH oxidase in neutrophils [21,22], macrophages [22,23], and endothelium [24] through inhibition of p47phox translocation [25], without interfering with other immune biological functions of cell systems. This is an important therapeutic mechanism of apocynin, as NADPH plays a crucial role in the complex cell-cell interaction during oxidative status [26].…”
Section: Discussionmentioning
confidence: 99%
“…These include: xanthine oxidase (Miyachi et al 1986;Satoh et al 1998;Fleming et al 2001), NADPH oxidase (Meyer et al 1999;Hohler et al 2000;Barry-Lane et al 2001;Beswick et al 2001;Seno et al 2001;Brandes et al 2002;Li et al 2002;Lassegue et al 2003;Parinandi et al 2003), and uncoupled NOS (Beretta et al 2003;Landmesser et al 2003). NADPH oxidase and uncoupled NOS are thought to be major…”
Section: Sources Of Reactive Oxygen Speciesmentioning
confidence: 99%